Güeros by Alonso Ruizpalacios: the trip as a recovery of the sense of reality as opposed to simulation - Rojas Pachas, Daniel (2023)
Güeros is a 2014 Mexican film directed by Alonso Ruizpalacios. The analysis of the film has as its theoretical framework the postulates of Gerard Genette and Jean Baudrillard on metalepsis and simulacrum respectively. This reading analyses the dichotomy between the real and the simulacra constructed by television and film images and focuses on the importance of the journey as a mechanism for the reconstruction of subjectivity, for this reason, it has been prioritized the transit experienced by the protagonist, Shadow, and his transformation into an observant subject and conscious participant of his time.